2013
DOI: 10.3382/ps.2012-02377
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone stress response of Greater Rhea (Rhea americana) during short-term road transport

Abstract: The effect of transport stress on blood corticosterone levels in captive Greater Rheas was investigated. Twelve adult individuals (7 males; 5 females) were loaded in pairs inside wooden crates and transported along a paved road for 30 min. Blood samples were taken before the individuals were introduced into the crate (baseline value) and immediately after they were unloaded (30 min after capture). To assess whether corticosterone levels were affected by the blood sampling procedure per se, another 6 (nontransp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
1
12
1
Order By: Relevance
“…However, in our 18-h transport study the posttransport corticostrone concentration was higher (6.9 ± 2.1 ng/mL) but not significantly different from the pretransport hormone level. The difference between our study versus the Mitchell et al (1996) and Lèche et al (2013) studies could be due to the difference in the transport duration in these 3 studies and the variability in the glucocorticoid concentrations in different stages of the stressful event (Dantzer and Mormède, 1983;Mounier et al, 2006) or their circadian secretion rhythm (Möstl and Palme, 2002). Mounier et al (2006) indicated that corticosteroids did not show the stress level for events that occurred several hours previously.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…However, in our 18-h transport study the posttransport corticostrone concentration was higher (6.9 ± 2.1 ng/mL) but not significantly different from the pretransport hormone level. The difference between our study versus the Mitchell et al (1996) and Lèche et al (2013) studies could be due to the difference in the transport duration in these 3 studies and the variability in the glucocorticoid concentrations in different stages of the stressful event (Dantzer and Mormède, 1983;Mounier et al, 2006) or their circadian secretion rhythm (Möstl and Palme, 2002). Mounier et al (2006) indicated that corticosteroids did not show the stress level for events that occurred several hours previously.…”
Section: Discussioncontrasting
confidence: 67%
“…Mitchell et al (1996) transported their ostriches for 4.5 h, and after transportation corticosterone concentrations increased by 75%. Lèche et al (2013) also reported a dramatic increase (40 times) in the corticosterone concentration of greater rhea (another member of the ratite family) after a 30-min transport. However, in our 18-h transport study the posttransport corticostrone concentration was higher (6.9 ± 2.1 ng/mL) but not significantly different from the pretransport hormone level.…”
Section: Discussionmentioning
confidence: 90%
“…Many researchers have considered plasma cortisol as an indicator of stress, and have found a significant increase in plasma cortisol concentration (Tischner and Niezgoda, 2000;Leche et al, 2013). In our study, a significant reduction of AR expression was found in transported mice, and this may indicate that Sertoli cells function changed greatly in the testis, but the complex mechanism is still unknown.…”
Section: Discussionsupporting
confidence: 54%
“…Numerous studies have documented the impacts of transportation on a variety of laboratory species (Arts et al, 2012;Browning and Leite-Browning, 2013;Chandurvelan et al, 2012;Lèche et al, 2013;Munsters et al, 2013;Stemkens-Sevens et al, 2009). Numerous studies have documented the impacts of transportation on a variety of laboratory species (Arts et al, 2012;Browning and Leite-Browning, 2013;Chandurvelan et al, 2012;Lèche et al, 2013;Munsters et al, 2013;Stemkens-Sevens et al, 2009).…”
Section: Stressorsmentioning
confidence: 99%